Zatoichi Meets the One-Armed Swordsman Based on a Short Story by Kan Shimozawa - Yasuda, Kimiyoshi; Makiura, Chishi; Morita, Fujio; Katsu, Shintaro; Wang-Yu, Jimmy; Hamaki, Watako (Zatoichi: The Blind Swordsman Collection, 2019)
It's East meets East when one of Japan's action idols crosses paths with an iconic kung-fu hero from Hong Kong. While traveling the countryside, Zatoichi comes across Wang Kang (Jimmy Wang Yu), a Chinese swordsman protecting a brutally orphaned young child. Despite the language barrier, the men forge a friendship, until nefarious enemies plant seeds of distrust to pit the two master martial artists against each other. [www.criterion.com]